Diagnostic Evaluation of Uterine Artery Doppler Imaging for the Prediction of Early Abnormal Pregnancy - Abdulla, Thikra N.; Hassan, Qays A.; Abood, Hawraa K. (AL-Kindy College Medical Journal, 2021)
Objective: to assess the predictive value of Doppler imaging of the uterine artery in the identification of early intrauterine abnormal pregnancy as compared to a normal intrauterine pregnancy.Subjects and methods: one hundred and twenty pregnant ladies, at their 6-12 weeks of gestation, with a singleton pregnancy were included in this population-based case-control study. Thirty women with a missed miscarriage, 30 with hydatidiform mole, 30 with a blighted ovum, and 30 as a control group, without risk factors, underwent Doppler interrogation of the uterine arteries. Resistive index (RI), pulsatility index (PI), and the systolic/diastolic ratio (S/D) were measured for both sides. The t-test, or ANOVA test when appropriate, was used to analyze the relationship between the variables.Results: there was a significant reduction of RI mean, PI mean, and S/D ratio among women with different types of abnormal pregnancy compared with the control group. RI and PI mean levels were significantly lower in women with hydatidiform mole and significantly higher in women with missed miscarriage. Lower left S/D mean level was significantly associated with hydatidiform mole and upper left S/D level was associated significantly with control women. For prediction of missed miscarriage; right and left uterine artery RI shows a sensitivity of 80%, 73.3%, a specificity of 68%, 71.1%, and the highest AUC was 0.78 for both.For prediction of molar pregnancy, right and left uterine artery RI showed a sensitivity of 63% for both, a specificity of 54.4%, 60%, and the highest AUC was 0.58, 0.61 respectively.Conclusions: Uterine artery Doppler ultrasonography at 6-12 weeks of gestation is predictive for early pregnancy complications such as missed abortion, hydatidiform mole, and blighted ovum.